Comparison of methods to determine CTOD for SENB specimens in different strain hardening steels. Issue 3 (11th October 2017) - Khor, W.L.; Moore, P.; Pisarski, H.; Brown, C.
Abstract: Methods for determining crack tip opening displacement (CTOD) given in national and international standards are compared for steels with a range of strain hardening characteristics. Crack tip opening displacement measurements were made from single‐edge notched bend notches using a silicone rubber casting method. The finite element model produced good agreements with predictions of these CTOD measurements. The versatility of the finite element model enabled CTOD from the original crack tip and the 45° intercept method to be compared. The 45° CTOD generally underestimates the original crack tip CTOD, and is less useful for conditions with stable crack extension. Apart from the high strain hardening material, CTOD calculated using BS 7448‐1, WES 1108 (JWES), and ASTM E1820 was slightly lower than the values determined from silicone measurements and modelling, which is conservative. ASTM E1820 gave the largest underestimation of CTOD, whilst BS 7448‐1 may be unsuitable for higher strain hardening steels, where the standard predicts higher CTOD than measured from the replica. JWES gives the most consistent estimation of CTOD for steels with a wide range of strain hardening values.